Political Identity Between Language and Power: A Comparative Philosophical Reading of the Thought of Al-Jahiz and Taha Abd al-Rahman - Dr. Hanan Ahmed Habib Habib (Journal of Scientific and Human Dimensions, 2026)
This study examines the problem of political identity between language and power from a philosophical and analytical perspective. It is grounded in the assumption that the crisis of political identity in the contemporary Arab context is not merely a crisis of belonging or institutional weakness, but fundamentally a normative crisis related to the nature of political discourse, sources of legitimacy, limits of power, and the horizon of moral responsibility. The study adopts a comparative approach between Al-Jahiz, as a foundational cultural and rational thinker, and Taha Abderrahmane, as a contemporary moral and normative philosopher. It argues that Al-Jahiz established a form of rational-bayani thinking that conceives language as a space for argumentation, debate, and critique of domination, rather than an instrument of symbolic power. This perspective leads to a conception of authority constrained by reason and proof, and to a political identity open to plurality and participation. Conversely, the study shows that Taha Abderrahmane advances the discussion to a deeper ethical level, where language becomes a morally entrusted act, authority is understood as responsibility rather than mere persuasion, and political identity is defined as a value-based practice grounded in accountability and testimony rather than procedural compliance. The study concludes that the relationship between the two approaches is not one of contradiction or rupture, but of philosophical complementarity, which allows for the construction of a contemporary Arab political identity based on the transition from domination to participation, from linguistic authority to moral responsibility, and from an identity of compliance to one of ethical agency. In doing so, the research contributes to renewing Arab political thought by re-linking language, power, and ethics, and by opening a new philosophical horizon for the study of political identity beyond closed traditional dichotomies.